Determination of mechanical behavior of shot peened valves / Mohd Khazairudin Azwadi Razali - Razali, Mohd Khazairudin Azwadi (2004)
The determination of mechanical behavior of shot peened automobile valves is to make the comparison between the strength and analyzed the behavior of the valve and concludes the performance of the valve. The surface treatment are done to make the observation of the types of failure occurred in the test made such as tensile which is to observed the ductile properties in the valves. Theoretical, experimental and results analysis was carried out through this study. Experimental result was obtained by using device known as INSTRON machine (tensile/compression), Rockwell hardness tester and Scanning Electron Microscopic machine. The results of the test from the experiment are then compared to make an analysis. Then, the comparison results were analyzed to determine the behavior of its properties which is the best valves that can be made from the treatment processes. However, the result shows that shot peened valves having the greater values from others which mean it indicates the performance of its applications. The valves having both processes heat treated and shot peened treatments are better than others as well it can improve the automobile industries in Malaysia.